"If It's Not Femicide, It's Still Murder": Contestations Over Femicide in Nicaragua. (January 2022) - Neumann, Pamela
Nicaragua has the dubious distinction of being one of the only countries in the world that has intentionally weakened its existing legislation penalizing the crime of femicide ( femicidio ), the murder of women due to their gender. Drawing on ethnographic fieldwork and content analysis of over 250 newspaper articles, this study examines how these legal changes occurred and their implications for women's access to legal justice in Nicaragua. Through an analysis of the competing claims of state officials and feminist actors, I demonstrate how femicidio became a contested legal and political category in Nicaragua, to the detriment of women's lives.